The impact of parent mediation on young children's home digital literacy practices and learning: A narrative review - Soyoof, Ali; Reynolds, Barry Lee; Neumann, Michelle; Scull, Janet; Tour, Ekaterina; McLay, Katherine (Journal of computer assisted learning, 2024)
Background In today's society, a growing body of literature attests to the importance of young children's early digital literacy skills in their home environments and how acquisition of these digital literacy skills relates to their future learning and digital literacy. Objectives Research on young children's digital literacy practices at home was reviewed to explore the positive and negative influences on early learning. This is important due to the children's rapid uptake of online digital technologies over the past decade. Methods Peer‐reviewed research articles on home digital literacy practices of children (aged 0–8 years old) published between 2010 and 2021 from four education databases were carefully selected based upon pre‐determined criteria and examined using content analysis. Results and Conclusion A high proportion of studies (29 of the 31; 93.5%) demonstrated significant benefits of young children gaining a range of skills, including digital operational, early literacy and language, socio‐emotional, and STEM, through the use of digital technologies at home. Five of the 31 (16.12%) studies reported negative effects of digital technologies in the home context, including distraction, aggressive behaviour, and false self‐confidence. Tablets and smartphone use gained greater momentum in the home context, especially between 2015 and 2021, and there was a positive shift in parental mediation, family involvement, and the children's home digital literacy practices. Implications By leveraging children's acquisition of digital literacy skills in the home and taking into account the sociocultural context, we can enhance young children's preparation for the future and provide opportunities for skill development across various learning domains. Lay Description What is already known about this topic The literature shows use of tablets in the home by children have gained momentum. Parents have different attitudes towards using digital technologies in the home context. Parents have used different mediation strategies to control, supervise and support their children's home digital literacy practices. What this paper adds Within the past decade, parents have extended their mediation strategies to support their children's home digital literacy practices. Young children move from early digital literacy to proficient digital literacy within the home. Home digital literacy practices can foster important skills in young children such as language and literacy, operational, socio‐emotional, and STEM. Artificial intelligence devices such as smart robots are extending children's home digital literacy practices. Implications for practice and/or policy Understanding the sociocultural differences of young children can help parents, teachers, and policymakers to facilitate digital literacy skill acquisition. Fostering young children's basic language literacy, operational, socio‐emotional, and STEM skills through technology use in the home before formal education is essential. Extending young children's home digital literacy practices to other contexts such as the classroom is necessary.